2013
DOI: 10.1128/aem.00062-13
|View full text |Cite
|
Sign up to set email alerts
|

Growth Media Simulating Ileal and Colonic Environments Affect the Intracellular Proteome and Carbon Fluxes of Enterohemorrhagic Escherichia coli O157:H7 Strain EDL933

Abstract: In this study, the intracellular proteome of Escherichia coli O157:H7 strain EDL933 was analyzed by two-dimensional gel electrophoresis and matrix-assisted laser desorption ionization-time-of-flight (MALDI-TOF) spectrometry after growth in simulated ileal environment media (SIEM) and simulated colonic environment media (SCEM) under aerobic and microaerobic conditions. Differentially expressed intracellular proteins were identified and allocated to functional protein groups. Moreover, metabolic fluxes were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…A considerable structural homology was found for the Gb3Cer and Gb4Cer lipoforms carrying ceramides composed of sphingosine (d18:1) and acyl chains with various chain lengths (C 16 , C 22 , and C 24 ) (Fig. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable structural homology was found for the Gb3Cer and Gb4Cer lipoforms carrying ceramides composed of sphingosine (d18:1) and acyl chains with various chain lengths (C 16 , C 22 , and C 24 ) (Fig. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…An RNeasy minikit (Qiagen, Hilden, Germany) was used for the extraction of total RNA from EHEC strains grown at 37°C in pooled, sterile-filtered (pore size, 0.2 m) human urine, LB, RPMI 1640 cell culture medium, or SCEM (22) for incubation periods of 2, 4, and 12 h. Residual coextracted DNA was removed from the purified RNA using an Ambion Turbo DNA-free kit (Life Technologies, Darmstadt, Germany). …”
Section: Methodsmentioning
confidence: 99%
“…In addition to looking at the ability of E. coli K-12 strains to utilize sialic acid, there have been studies comparing carbon metabolism between K-12 and pathogenic EDL933 O157:H7 strains (9, 30, 95). A carbon metabolism comparison between these two strains demonstrated a similar but not identical preference of nutrients in vitro , with both strains having Neu5 A c as their 4 th most preferred nutrient (30).…”
Section: Utilization Of Sialic Acid As a Carbon Source By Intestinal mentioning
confidence: 99%
“…Therefore, many of the primers used in this study (see Table S1 in the supplemental material) were named according to the locus tags used in that sequence entry. Recent work was based on this sequence and the nomenclature that we used was also applied accordingly, e.g., gene locus z1466, plasmid pET-z1466-his (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Herold et al (13), it was shown that the corresponding ORF of phage 933W and other phages was expressed upon norfloxacin induction. Later on, the corresponding 933Wp42 protein was identified as the most prominently regulated protein, with 40-fold overexpression in simulated colonic environmental medium (SCEM) under aerobic conditions in strain EDL933 (14). Consequently, protein 933Wp42 was recombinantly produced from laboratory E. coli strain C600/933W and demonstrated cleavage of 5-N-acetyl-9-O-acetyl neuramininic acid (Neu5,9Ac 2 ) (15).…”
mentioning
confidence: 99%